Southern brown bandicoots can be successfully returned to the wild after physiological experiments. - Cooper, Christine (2011)
Context -- The poor survivorship of many animals released into the wild for translocation, re-introduction or rehabilitation may be cited as a reason not to release experimental animals, but there is only limited information available on the fate of ex-research animals returned to the wild. Aims -- This study tested the hypothesis that there was no difference in the recapture of bandicoots used for physiological experiments and control bandicoots. Methods -- Six adult male bandicoots were trapped and maintained in captivity for three weeks for physiological experiments, then released at the capture site. Sixteen other bandicoots were captured and released immediately. Seven weeks after the release of the bandicoots used for physiological studies, follow-up trapping was carried out, and the survival, body mass and distance moved of recaptured bandicoots was recorded. Key results -- Survivorship did not differ statistically for bandicoots used for physiological experiments and control bandicoots, with five of six experimental bandicoots (83 %) and 11 of 16 control bandicoots (69%) recaptured. Bandicoots used for physiological experiments lost a significantly greater proportion of body mass than control animals, but this occurred in captivity, not after release. The distance between recaptures for both groups (0-224m) was consistent with previously published observations.Conclusions -- My results suggest that bandicoots maintained in captivity for non-invasive physiological experiments can be successfully released, with survivorship at least as high as that of control animals. Implications -- This study provides researchers, wildlife managers, and animal ethics committees with information to assist with making judgements concerning the fate of ex-research animals.